The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1999
DOI: 10.1111/j.1553-2712.1999.tb00119.x
|View full text |Cite
|
Sign up to set email alerts
|

Fast Track and the Pediatric Emergency Department: Resource Utilization and Patient Outcomes

Abstract: Abstract. Objective: To examine differences in the evaluation, management, and outcomes for patients seen in an on-site ''fast track'' (FT) vs the main ED. Methods: Over a three-month period, patients presenting to an urban pediatric ED were prospectively assessed. Patients included were: triaged as ''nonurgent''; aged 2 months to 10 years; not chronically ill; and had fever, or complaint of vomiting, diarrhea, or decreased oral intake. Evening and weekend care was provided in the FT; at all other times these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 20 publications
0
30
0
Order By: Relevance
“…Given that about 80% of ED visits are non-urgent, the use of an ED fast track lane is a great aid in serving lower acuity patients and reducing Downloaded by [Stockholm University Library] at 05:34 12 August 2015 overcrowding (Williams, 2006). Fast track implementation has found success in numerous ED environments, such as in an urban pediatric ED (Simon et al, 1996;Hampers et al, 1999), or a teaching hospital (Meislin et al, 1988). Roche and Cochran (2007) apply a queueing methodology to eight EDs, implementing fast tracks with different patient acuity, volume, and anticipated LOS in an effort to minimize patients LWBS.…”
Section: Ed Fast Trackmentioning
confidence: 98%
“…Given that about 80% of ED visits are non-urgent, the use of an ED fast track lane is a great aid in serving lower acuity patients and reducing Downloaded by [Stockholm University Library] at 05:34 12 August 2015 overcrowding (Williams, 2006). Fast track implementation has found success in numerous ED environments, such as in an urban pediatric ED (Simon et al, 1996;Hampers et al, 1999), or a teaching hospital (Meislin et al, 1988). Roche and Cochran (2007) apply a queueing methodology to eight EDs, implementing fast tracks with different patient acuity, volume, and anticipated LOS in an effort to minimize patients LWBS.…”
Section: Ed Fast Trackmentioning
confidence: 98%
“…In another study the median length of stay was 36 minutes for fasttracked patients compared with 63 minutes for the control group [63]. This has worked equally well in pediatric units [64]. A recent study [65] of a fast-track unit also demonstrated an improvement in length of stay from 127 to 53 minutes (P < 0.001).…”
Section: Question 4: In Hospital Eds Experiencing Overcrowding (Settimentioning
confidence: 64%
“…For example, fast track EDs and urgent care centers may locate offsite from the hospital and specialize in relatively quick turnaround of low-acuity patients. These centers have shown some ability to manage patients quicker than regular EDs, and with a lower cost, [19][20][21][22] although these results are not adjusted for patient severity. Furthermore, once introduced to the concept of urgent care, patients often realize that such sites can meet many of their needs, and they may make fewer visits to the ED.…”
Section: Potential Changes In Reimbursement For Ed Servicesmentioning
confidence: 90%